2008
DOI: 10.1007/s00266-008-9166-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Sildenafil and Vascular Endothelium Growth Factor Combination Treatment on Skin Flap Survival in Rats

Abstract: The combination of sildenafil and VEGF decreases the extent of avascular and stasis zones in skin flaps. The skin flap improvement seen with the combination treatment was similar to the sildenafil treatment alone suggesting that enhanced flap survival was due solely to the effect of sildenafil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…Several rat studies [18][19][20][21] note that sildenafil can improve the viability of random pattern flaps; by extrapolation, we felt that two of our flaps could possibly benefit from this pharmacologic action. While there is no proof that the sildenafil truly did improve the flow of these flaps, we felt anecdotally that it did improve the internal blood flow and abrogated the formation of fat necrosis in these two flaps that otherwise might have developed fat necrosis.…”
Section: Discussionmentioning
confidence: 92%
“…Several rat studies [18][19][20][21] note that sildenafil can improve the viability of random pattern flaps; by extrapolation, we felt that two of our flaps could possibly benefit from this pharmacologic action. While there is no proof that the sildenafil truly did improve the flow of these flaps, we felt anecdotally that it did improve the internal blood flow and abrogated the formation of fat necrosis in these two flaps that otherwise might have developed fat necrosis.…”
Section: Discussionmentioning
confidence: 92%
“…Even though Tsai et al 10 applied sildenafil by the intraperitoneal pathway daily, the subdermal use of the growth factor was done only once, right after the skin flap was made.…”
Section: Resultsmentioning
confidence: 99%
“…Some auxiliary therapeutic resources were proposed in the attempt to improve flap survival, such as autonomization 1 , intramuscular use of ketorolac 2 , corticosteroids and carnitine 3 , hyperbaric oxygen therapy 4 , pentoxifylline 5 , buflomedil 6 , and even sildenafil isolated or in association with endothelial vascular growth or fibrin glue [7][8][9][10][11] . However, response to these systemic treatments may be associated with adverse effects, for example hypotension, amnesia, visual disturbances, migraine and even vascular accidents 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study (31), distally based dorsal skin flaps investigating sildenafil showed dose-dependent effects on random flap survival in rats, with higher doses and shorter intervals increasing efficacy. When examining the combined effects of sildenafil and vascular endothelial growth factor, the group receiving sildenafil and vascular endothelial growth factor in combination was not significantly different from the group of rats treated with sildenafil only, suggesting that the enhanced flap survival was only due to the effect of sildenafil (32). Timing of the beneficial effects of sildenafil has also been studied; administration of sildenafil may be more important in early rather than later postoperative skin flap viability (33).…”
Section: Sildenafil In Ischemic Animal Studiesmentioning
confidence: 99%